Gallium oxide doped argyrodite solid electrolyte and preparation method and application thereof

By doping gallium oxide into the sulfur silver germanium ore electrolyte, a solid electrolyte with high ionic conductivity and optimized air stability and interface compatibility was prepared, which solved the problem of poor air stability and interface compatibility of sulfur silver germanium ore electrolyte, and significantly improved the performance and stability of all-solid-state batteries.

CN119674201APending Publication Date: 2025-03-21WENZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411886049.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The air stability and interface compatibility of the solid electrolyte of sulfur silver germanium ore are poor, affecting the cycling performance of the battery.

Method used

By doping gallium oxide (Ga2O3) into the sulfur silver germanium ore electrolyte, a solid electrolyte of Li6.1P0.95Ga0.05S4.925O0.075Cl was prepared, and the ball milling method and solid-phase sintering method were used for preparation.

Benefits of technology

It improves the air stability and interface compatibility of solid electrolytes, enhances lithium ion transmission capabilities, and significantly improves the performance and stability of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674201A_ABST
    Figure CN119674201A_ABST
Patent Text Reader

Abstract

The invention provides a gallium oxide doped argyrodite solid electrolyte as well as a preparation method and application thereof. The chemical formula of the gallium oxide doped argyrodite solid electrolyte is Li < 6.1 > P < 0.95 > Ga < 0.05 > S < 4.925 > O < 0.075 > Cl. The solid electrolyte is prepared by a ball milling method and a solid phase sintering method, the successful doping of Ga2O3 is proved by XRD (X-Ray Diffraction), Raman spectrum, XPS (X-Ray Photoelectron Spectroscopy) and other technologies, and meanwhile, the doped electrolyte LPSC-0.05 shows relatively high ionic conductivity and air stability. In addition, a cyclic voltammetry (CV) test, a critical current density (CCD) test and a constant current charging and discharging test are performed aiming at the problem of a negative electrode interface, and the interface compatibility is superior to that of an undoped sample. And finally, CV, impedance, rate and long-cycle tests are carried out on the all-solid-state battery, and the battery assembled by using the LPS-0.05 can show better performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state battery preparation, and in particular to a gallium oxide-doped argyrodite solid electrolyte and a preparation method and application thereof. Background Art

[0002] Sulfide solid electrolytes have attracted widespread attention due to their incomparable advantages over other types of electrolytes. Argentite electrolytes, which have high ionic conductivity and stable electrochemical windows, are favored by a large number of researchers as a typical representative of sulfide solid electrolytes. Although argyrodite solid electrolytes have the above-mentioned outstanding advantages, their poor air stability and lithium compatibility issues cannot be underestimated. The reason is that the chemical properties of argyrodite solid electrolytes themselves are relatively active, and they will react with lithium transition metal oxides (such as LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 On the negative electrode side, it will also react with lithium to form byproducts such as lithium sulfide and lithium phosphide, and may further cause uneven lithium metal deposition, leading to the growth of lithium dendrites, piercing the electrolyte, and causing internal short circuits in the battery. The above problems will seriously affect the cycle performance of the battery, so it is extremely important to develop a solid electrolyte with high ionic conductivity and optimized air stability and interface compatibility.

[0003] In order to solve the above problems, many scholars have conducted in-depth research. Element doping of sulfide solid electrolytes is the simplest and most efficient strategy. So far, many researchers have doped sulfide solid electrolytes with nitrides and halides. On the one hand, element doping promotes the formation of crystal defects, adjusts the space charge layer, and promotes lithium ion transmission; on the other hand, the stability of sulfide solid electrolytes can be improved by introducing moisture-resistant and stable elements. However, due to the presence of N 3– It is also easily hydrolyzed. – The introduction of (halide ions) into the argyrodite electrolyte does not replace the anions, so in order to achieve both high ionic conductivity and air stability, it is necessary to further search for better dopants. Summary of the invention

[0004] The present invention aims to provide a gallium oxide doped argyrodite solid electrolyte and a preparation method and application thereof, so as to solve the technical problems of poor air stability and poor interface compatibility of the argyrodite solid electrolyte.

[0005] To achieve the above object, the present invention provides a gallium oxide doped argyrodite solid electrolyte, the chemical formula of which is Li 6.1 P 0.95 Ga 0.05 S4.925 O 0.075 Cl.

[0006] The present invention also provides a method for preparing the aforementioned gallium oxide-doped argyrodite solid electrolyte, which comprises mixing Li2S, P2S5, LiCl, and Ga2O3, ball-milling the mixture, cold-pressing the mixture into sheets, sintering the mixture at high temperature, naturally cooling the mixture to room temperature, grinding the mixture, and sieving the mixture to obtain the solid electrolyte.

[0007] As one of the preferred technical solutions, the molar ratio of Li2S, P2S5, LiCl and Ga2O3 is 5.1:0.95:2:0.05.

[0008] As one of the preferred technical solutions, the ball milling conditions are: first set 200r / min forward rotation for 1 hour, pause for 30 minutes, reverse for 1 hour, pause for 30 minutes, and continuously cycle, and accumulate low-speed ball milling for 10 hours to mix the raw materials evenly, and then set 400r / min forward rotation for 1 hour, pause for 30 minutes, reverse for 1 hour, pause for 30 minutes, and continuously cycle, and accumulate high-speed ball milling for 40 hours.

[0009] As one of the preferred technical solutions, the specific method of cold pressing into tablets is: cold pressing into tablets using a tablet press at 250 MPa, and maintaining the pressure for 3 to 5 minutes.

[0010] As one of the preferred technical solutions, the specific method of high-temperature sintering is: use a tubular furnace for sintering, set the time from room temperature (30°C) to 500°C to 235 minutes, set the heating rate to 2°C / min, keep at 500°C for 300 minutes, and then cool naturally to room temperature.

[0011] As one of the preferred technical solutions, the powder is ground in a mortar until it is uniform and then sieved with a 400-mesh sieve.

[0012] The present invention also provides the use of the above-mentioned solid electrolyte in the preparation of composite positive electrode materials.

[0013] The present invention provides a composite positive electrode material, comprising the above-mentioned solid electrolyte.

[0014] As one of the preferred technical solutions, the composite positive electrode material is obtained by mixing and grinding polycrystalline NCM811 (LNO@NCM811) coated with LiNbO3, the above-mentioned solid electrolyte and a conductive additive.

[0015] As one of the further preferred technical solutions, the mass ratio of LNO@NCM811, solid electrolyte and conductive additive is 70:29:1, and the grinding time is 20 minutes.

[0016] As one of the further preferred technical solutions, the conductive additive is acetylene black.

[0017] The present invention also provides the use of the above-mentioned solid electrolyte or composite positive electrode material in the preparation of a solid-state battery.

[0018] The present invention also provides a solid-state battery, comprising a positive electrode made of the above-mentioned composite positive electrode material.

[0019] The present invention has the following beneficial effects:

[0020] As an excellent semiconductor material, gallium oxide has always attracted much attention for its conductivity and luminescence properties, and has broad application prospects in electronic devices. First of all, gallium oxide has a wide energy band gap of about 4.5 to 5.0 eV, which enables it to provide a good ion transport path in solid electrolytes while inhibiting the transport of electrons. In addition, gallium oxide also has good thermal stability and chemical stability. It will not undergo structural changes and side reactions during material preparation and battery cycling, while improving the overall stability of the material and battery. Relevant studies have shown that because O and S are in the same family and have similar chemical properties, O 2– The introduction of 2– The site, and O 2– Moisture resistance ratio S 2– Better, introduce O 2– After that, the material's air stability will increase. 3+ As a positively charged metal ion, Ga 3+ and P 5+ Both have the properties of soft acid. If Ga 3+ Replaced P 5+ , Ga 3+ Compared with P 5+ Larger ionic radius, and Ga 3+ The charge number is less than P 5+ The charge number, so according to the theory of hard and soft acid and base, compared with P 5+ , Ga 3+ is a softer acid, while S 2- is a softer base, then the bonding strength of Ga–S is theoretically greater than that of P–S bonds, which makes the stability to water molecules enhanced after doping. 3+ The introduction of will cause lattice expansion and promote lithium ion transport.

[0021] The present invention prepares Li by ball milling and solid phase sintering. 6+2x P 1-x Ga x S 5-1.5x O 1.5xCl (for the convenience of writing and reading, the sample with x=0 will be abbreviated as LPSC, and the samples with other proportions will be abbreviated as LPSC-x) argyrodite sulfide solid electrolyte, and the successful doping of Ga2O3 was confirmed by XRD, Raman spectroscopy and XPS. At the same time, the electrolyte LPSC-0.05 after doping showed high ionic conductivity and air stability. In addition, cyclic voltammetry (CV) test, critical current density (CCD) test and constant current charge and discharge test were carried out for the negative electrode interface problem, all of which showed better interface compatibility than undoped samples. Finally, CV, impedance, rate and long cycle tests were carried out on all-solid-state batteries, and the batteries assembled using LPSC-0.05 showed better performance. The present invention provides new ideas and methods for the subsequent development of sulfide solid electrolytes, promotes the development of solid electrolytes and solid-state batteries, and further accelerates the commercialization of solid-state batteries that are safer than traditional liquid batteries.

[0022] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0024] Figure 1 XRD spectra, where (a) XRD spectra of sulfide solid electrolytes with different doping ratios; (b) Figure 1 (a) A partial enlarged view.

[0025] Figure 2 Raman spectra of LPSC sulfide solid electrolytes with different doping ratios.

[0026] Figure 3 XPS P2p spectra, including: (a) XPS P2p spectrum of LPSC sulfide solid electrolyte; (b) XPS P2p spectrum of LPSC-0.05 sulfide solid electrolyte.

[0027] Figure 4 are SEM morphology images, where (a) and (b) are SEM morphologies of LPSC solid electrolyte; (c) and (d) are SEM morphologies of LPSC-0.05 solid electrolyte.

[0028] Figure 5 The microstructure and element mapping of LPSC-0.05 solid electrolyte.

[0029] Figure 6These are the EIS test results, including: (a) impedance spectrum of LPSC-x at room temperature; (b) ionic conductivity of LPSC-x at room temperature; (c) Arrhenius curve of LPSC-x; (d) activation energy of LPSC-x.

[0030] Figure 7 These are the results of DC polarization tests, including: (a) DC polarization curve of LPSC-x; (b) electronic conductivity of LPSC-x.

[0031] Figure 8 Air stability test, including: (a) hydrogen sulfide generation of LPSC-x; (b) ion conductivity retention of LPSC and LPSC-0.05.

[0032] Fig. 9 CV test, where (a) CV curve of Li / SSE / SS asymmetric battery; (b) Fig. 9 (a) Partial magnification.

[0033] Fig.10 Critical current density test, including: (a) Li / LPSC / Li critical current density test; (b)

[0034] Li / LPSC-0.05 / Li critical current density test.

[0035] Fig.11 Constant current charge and discharge test for Li / LPSC / Li and Li / LPSC-0.05 / Li symmetric batteries.

[0036] Fig.12 Impedance spectra of NCM811 / LPSC / Li (a) and NCM811 / LPSC-0.05 / Li (b) full batteries before and after cycling.

[0037] Fig.13 CV curves of full cells NCM811 / LPSC / Li (a) and NCM811 / LPSC-0.05 / Li (b).

[0038] Fig.14 Full cell rate performance of NCM811 / LPSC / Li and NCM811 / LPSC-0.05 / Li.

[0039] Fig.15 Long cycle performance of NCM811 / LPSC / Li and NCM811 / LPSC-0.05 / Li full batteries. DETAILED DESCRIPTION

[0040] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0041] 1. Preparation of sulfide solid electrolyte

[0042] Li2S, P2S5, LiCl, Ga2O3 are separated according to the chemical equation (5+2x)Li2S+(1-x)P2S5+2LiCl+x Ga2O3→2Li 6+2x P 1-x Ga x S 5-1.5x O 1.5x The mass of each reaction raw material is calculated from the stoichiometric ratio of Cl, m(Li2S)=(230+92x)y; m(P2S5)=(222-222x)y; m(LiCl)=85y; m(Ga2O3)=188xy, wherein x represents the doping amount of Ga element, and y represents the proportional coefficient, specifically, x=0.05, y=1.852, m(Li2S)=434.5mg, m(P2S5)=391mg, m(LiCl)=157mg, and m(Ga2O3)=17.5mg. The material is then placed in a ball mill, first set to 200r / min forward rotation for 1 hour, pause for 30 minutes, reverse for 1 hour, pause for 30 minutes, and continuously cycle, accumulating low-speed ball milling for 10 hours to mix the raw materials evenly, and then set to 400r / min forward rotation for 1 hour, pause for 30 minutes, reverse for 1 hour, pause for 30 minutes, and continuously cycle, accumulating high-speed ball milling for 40 hours. The ball-milled powder is cold-pressed into a sheet, and then the electrolyte sheet is placed in a quartz tube for high-temperature sintering for 10 hours. After the obtained electrolyte sheet is cooled to room temperature, it is placed in a mortar for grinding and sieving for subsequent use.

[0043] 2. Preparation of composite cathode materials

[0044] LiNbO3-coated polycrystalline NCM811 (LNO@NCM811, purchased from Mengguli New Energy Co., Ltd.), argyrodite solid electrolyte and conductive additive acetylene black were placed in a mortar at a ratio of 70:29:1 (mass ratio) and ground for 20 minutes to obtain a composite positive electrode material.

[0045] 3. Physical characterization of materials

[0046] The crystal structure of the material was characterized using an X-ray diffractometer with a scanning rate of 2° / min, a voltage parameter of 40kV, a current parameter of 40mA, and a scanning range of 10-80°. The prepared sulfide solid electrolyte sample was placed on the XRD stage in a glove box and encapsulated with a polyimide film.

[0047] The chemical bonds of the materials were characterized using a confocal Raman spectrometer with a 532nm excitation source and a 20× microscope lens, with a scanning range of 100 to 1000 cm–1 .

[0048] The air exposure test was carried out in an ambient atmosphere with a humidity of 70%. 10 mg of sulfide solid electrolyte was placed at 36900 cm 3 In a sealed container, the air humidity is 70%, and a hydrogen sulfide detector is placed in the container for testing, recording every 5 minutes and testing for 1 hour.

[0049] The morphology and chemical composition of the material surface were analyzed using a scanning electron microscope (SEM) equipped with energy dispersive spectroscopy (EDS). The electronic structure of the material was characterized using an X-ray photoelectron spectroscopy (XPS).

[0050] 4. Electrochemical characterization of materials

[0051] The test frequency range of electrochemical impedance spectroscopy (EIS) is 0.1Hz~100000Hz, and the amplitude is 50mV. First, the sulfide solid electrolyte powder is loaded into a specific battery mold, cold pressed into sheets under a pressure of about 250MPa, and finally connected to the electrochemical workstation for testing. Steel sheets (SS), lithium sheets (Li) and sulfide solid electrolytes (SSE) are used to assemble SS / SSE / Li assembled asymmetric batteries for CV testing. The test voltage range is -0.5~5V, and the scan rate is 5mV / s. In order to evaluate the compatibility of the electrolyte with metallic lithium, the constant current charge and discharge method is adopted for the Li / SSE / Li symmetric battery. The electronic conductivity of the prepared sulfide solid electrolyte is tested by the DC polarization method.

[0052] 5. Assembly of all-solid-state batteries

[0053] For the assembly of NCM811 / LPSC-x / Li all-solid-state battery, the sulfide solid electrolyte was firstly subjected to a pressure of about 250 MPa and cold pressed for 5 min. Then, the prepared composite cathode was loaded into the battery mold with an active material loading of 9.8 mg cm –2 , and maintained at a pressure of 250MPa for 5 minutes; a lithium sheet was attached to the other side, and finally a copper foil was used as a current collector on the negative electrode side, and cold pressed at a pressure of 93.6MPa for 1.5 minutes. The charge and discharge experiments of NCM811 / LPSC-x / Li battery were carried out at a current density of 0.117~0.586mAcm –2 , voltage range is 2.8~4.3V(vs.Li / Li + ). The impedance of the battery is measured in the frequency range of 0.1 Hz to 100,000 Hz and the voltage is 50 mV. The specific capacity value is evaluated by the mass of the active material.

[0054] 6. Results and Discussion

[0055] 6.1Li6+2x P 1-x Ga x S 5-1.5x O 1.5x Structural and morphological characterization of Cl

[0056] Figure 1 The X-ray diffraction (XRD) patterns of LPSC-x (x = 0, 0.05, 0.1, 0.15, 0.2) can be observed from the figure that with the increase of doping ratio, the XRD diffraction peak of the solid electrolyte gradually shifts to a low angle, which means that the unit cell undergoes lattice expansion, and also proves the successful incorporation of Ga2O3. In addition, it can be found through observation that the diffraction peak of the original crystal in the XRD pattern has not disappeared, indicating that the original unit cell structure has not been destroyed, but as the amount of dopant continues to increase, more defects are brought to the original crystal structure, resulting in a continuous weakening of the diffraction peak intensity.

[0057] Raman measurements were performed on LPSC-x (x = 0, 0.05, 0.1, 0.15, 0.2) samples. Figure 2 It can be observed that the PS4 3- Raman peak at 420cm –1 、570cm –1 There are characteristic peaks near the PS4, and no peak splitting or new peak generation occurs, which indicates that Ga2O3 doping does not change the 3- However, since the electronegativity of Ga and P is different from that of O and S, when Ga 3+ Replace P 5+ , O 2– Replace S 2– After that, it will cause lattice distortion / disorder, resulting in different PS bond strengths, so the intensity and displacement of the Raman peak will fluctuate slightly. In addition, for the doped samples, the applicant -1 A weak characteristic peak of Ga-S bond was observed, which can indicate that Ga partially replaced P.

[0058] XPS tests and analyses were performed on LPSC and LPSC-0.05 sulfide solid electrolytes. Figure 3 The applicant found that a new weak peak appeared in the P 2p of LPSC-0.05, which can be attributed to the PO bond, which can also prove that O successfully replaced part of S.

[0059] SEM and EDS tests are important means of characterizing the surface morphology and structure of materials and analyzing the composition. LPSC and LPSC-0.05 solid electrolytes were selected for SEM and EDS tests and analysis. Figure 4The SEM images of LPSC and LPSC-0.05 solid electrolytes at 50 and 20 μm, respectively. The results show that the particle size distribution of LPSC-0.05 solid electrolyte is uniform, without obvious agglomeration. In contrast, LPSC particles are larger and have obvious agglomeration.

[0060] The element distribution of LPSC-0.05 was further analyzed by EDS mapping. Figure 5 As shown in the figure, P, S, Cl, O, and Ga elements are evenly distributed without any enrichment, which proves that Ga is successfully doped into Li6PS5Cl.

[0061] 6.2Li 6+2x P 1-x Ga x S 5-1.5x O 1.5x Electrochemical performance and air stability of Cl

[0062] In order to compare the ionic conductivity of sulfide solid electrolytes at different doping ratios, the EIS AC impedance test was performed on the materials. Figure 6 (a) and (b) show the impedance spectra and ionic conductivity of sulfide solid electrolytes at different doping ratios. The ionic conductivity of LPSC is 1.33 mS cm –1 , while the ionic conductivity of LPSC-0.05 is 1.81 mS cm –1 As the amount of Ga2O3 doping increases, the ionic conductivity of the electrolyte shows a trend of attenuation. The improvement of electrolyte ionic conductivity can be attributed to the increase of Ga 3+ The incorporation of Ga2O3 expands the lattice and widens the lithium ion migration channel, but when the amount of Ga2O3 incorporation exceeds a certain critical point, the ionic conductivity will be reduced. This may be because O has a greater electronegativity than S, and has a greater binding force on lithium ions, which is not conducive to the migration of lithium ions. Figure 6 As shown in FIG. 1 , at temperatures of 25, 35, 45, 55, and 65°C, the impedance test was performed on electrolytes with different doping ratios. The obtained data were converted into ionic conductivity, and lnσ and 1000 / T were plotted to obtain the Arrhenius curve ( Figure 6 (c)), and then the activation energy is obtained by calculating the slope ( Figure 6 (d) Among them, the LPSC-0.05 electrolyte exhibits the smallest activation energy, which is only 0.182 eV, indicating that the energy barrier overcome by lithium ions when migrating through LPSC-0.05 is the lowest.

[0063] In addition, in order to further evaluate the electrochemical performance of the electrolyte, the applicant also conducted a DC polarization test to test its electronic conductivity. Figure 7(a) is the DC polarization curve. By applying a constant voltage, the current first decreases and then reaches a steady state. Finally, the electronic conductivity is calculated based on the steady-state current. Figure 7 (b). After doping with Ga2O3, the electronic conductivity of the electrolyte decreases, indicating that the conductivity of the electrolyte decreases after modification. During the battery cycle, Li + The possibility of electrons being reduced to form metallic lithium during migration is reduced, which means that Ga2O3 doping can alleviate the growth of lithium dendrites to a certain extent.

[0064] Sulfide solid electrolytes are extremely unstable when in contact with water, which is an urgent problem to be solved. The PS bonds in sulfide solid electrolytes break when they encounter water molecules and generate PO bonds, while releasing hydrogen sulfide gas. After Ga2O3 doping, since S is partially replaced by O, and the bond between Ga and S is stronger than that between P and S, it can alleviate the generation of H2S to a certain extent. Figure 8 (a) shows the volume of H2S released per unit mass of electrolytes with different doping ratios within 1 hour at 25°C and 70% humidity, indicating that the air stability of the electrolyte is indeed greatly improved after doping with gallium oxide. Figure 8 (b) shows the ionic conductivity retention rate after exposure to 70% air humidity for 20 minutes. The retention rate of LPSC-0.05 is higher than that of LPSC.

[0065] 6.3Li 6+2x P 1-x Ga x S 5-1.5x O 1.5x Anode interface compatibility of Cl

[0066] In order to evaluate the effect of Ga2O3 doping on the interfacial compatibility of lithium anode, the CV curves of Li / SSE / SS asymmetric cells were first tested. Fig. 9 As shown in (a), the electrolyte shows a pair of redox peaks near 0 V, corresponding to Li + Embedding (Li + +e - →Li) and Li + Escape (Li-e - →Li + ). Further, by observing the local amplification of 2.5~5V ( Fig. 9 In (b), LPSC has a more active current response, while LPSC-0.05 is relatively stable, indicating that LPSC may have side reactions with the lithium negative electrode, which is alleviated after the incorporation of Ga2O3.

[0067] The critical current density of the electrolyte was further determined by cycling the Li / SSE / Li symmetric cell at room temperature with a gradient current density. Fig.10 (a) is the polarization voltage curve of Li / LPSC / Li battery cycled at different current densities. The current density corresponding to the voltage drop is considered to be the critical current density for the formation of lithium dendrites in the electrolyte, and its size is used to evaluate the ability of the electrolyte to inhibit lithium dendrites. Fig.10 As shown in (b), the critical current density of the symmetric battery assembled using LPSC-0.05 is 1.2 mA cm –2 Compared with the undoped 0.5 mA cm –2 It is much higher. This shows that Ga2O3 doping can improve the stability of the negative electrode interface.

[0068] In addition, the compatibility of the electrolyte with the negative electrode before and after modification was further studied by constant current charge and discharge tests on Li / SSE / Li symmetric batteries. The current density was set to 0.2 mA cm –2 .like Fig.11 As shown in the figure, it can be seen that the stability of the Li / LPSC / Li symmetric battery is very poor. After 130 hours of cycling, there is a sudden drop in overvoltage, which may be caused by a short circuit caused by the unstable interface between the lithium negative electrode and the solid electrolyte. The Li / LPSC-0.05 / Li symmetric battery can be cycled for 350 hours, indicating that the compatibility of the doped electrolyte with the lithium negative electrode is greatly improved.

[0069] 6.4NCM811 / Li 6+2x P 1-x Ga x S 5-1.5x O 1.5x Cl / Li all-solid-state battery performance

[0070] In order to further illustrate the advantages of LPSC-0.05 in improving the performance of all-solid-state batteries, an all-solid-state lithium metal battery was assembled using mold cold pressing with NCM811 as the positive electrode and Li as the negative electrode. Fig.12 This is the electrochemical impedance spectrum of the battery before and after cycling. The impedance of the NCM811 / LPSC / Li battery increases significantly after the cycle, while the impedance increase of the NCM811 / LPSC-0.05 / Li all-solid-state battery is relatively small, which to some extent explains that the battery has better stability and reversibility after doping with Ga2O3.

[0071] In addition, CV tests were also performed on NCM811 / LPSC / Li and NCM811 / LPSC-0.05 / Li all-solid-state batteries. Fig.13As shown in the figure, the full battery assembled with LPSC-0.05 electrolyte corresponds to three oxidation peaks, located at 3.82, 4.05 and 4.22V, respectively. At the same time, these three peaks correspond to the transformation of the positive electrode material from H1 phase to M phase, M phase to H2 phase, and H2 phase to H3 phase, respectively. The coincidence is very high in 5 cycles, which reflects the excellent reversibility of the battery, which is also consistent with the change of the battery impedance mentioned above. In contrast, the full battery assembled with LPSC has a lower coincidence than that after doping, and the oxidation peaks corresponding to the three phase changes cannot be clearly observed. This may be because the side reactions at the interface between the electrolyte and the positive electrode are reduced after doping, and the positive electrode active material reacts more completely.

[0072] Fig.14 The rate performance of NCM811 / LPSC / Li and NCM811 / LPSI-0.05 / Li all-solid-state batteries was demonstrated. The discharge specific capacities of NCM811 / LPSC / Li batteries at rates of 0.1, 0.2, 0.3, 0.5, and 1C were 130, 112, 100, 82, and 50 mAh g, respectively. –1 When the C is returned to 0.1C, the specific capacity is 115 mAh g –1 The discharge specific capacities of NCM811 / LPSC-0.05 / Li battery at rates of 0.1, 0.2, 0.3, 0.5, and 1C are 138, 122, 110, 95, and 70 mAh g, respectively. –1 When the C is returned to 0.1C, the specific capacity can be restored to 123 mAh g –1 , which indicates that the full cell based on LPSC-0.05 electrolyte has good rate performance.

[0073] In order to further verify the cycle stability of the assembled all-solid-state battery, a long cycle test at a rate of 0.5C was carried out on the NCM811 / LPSC / Li and NCM811 / LPSC-0.05 / Li full batteries. Fig.15 As shown in Figure 2, after gradient activation from 0.1C to 0.5C, the initial specific capacity of the NCM811 / LPSC-0.05 / Li full battery is 135.68 mAh g –1 After 200 stable cycles, the specific capacity is still 123.85 mAh g –1 , the capacity retention rate reached 91.2%. In contrast, the initial specific capacity of NCM811 / LPSC / Li all-solid-state battery is only 89.06mAh g –1 After 200 cycles, the capacity retention rate is 67.3%. The above results all show that Ga2O3-doped sulfide solid electrolyte can significantly improve the performance of all-solid-state lithium batteries.

[0074] 7. Summary

[0075] The present invention prepares sulfide solid electrolytes LPSC and LPSC-0.05 by high-energy ball milling combined with solid phase sintering, and analyzes the effects of different doping amounts on the electrolyte structure and performance by means of physical and electrochemical characterization. 2– Replace S 2– , in Ga 3+ Replace P 5+ , and further explored the improvement of chemical stability and electrochemical performance after dual doping.

[0076] First, XRD and Raman tests proved that Ga2O3 was successfully doped into the original argyrodite electrolyte. Further ionic conductivity tests showed that the optimal doping ratio was x = 0.05, and the ionic conductivity of LPSC-0.05 was 1.81 mS cm –1 , compared with 1.33 mS cm of LPSC –1 Slightly improved. By testing the air stability of electrolytes prepared with different doping ratios, it was found that with the increase of doping amount, the electrolyte's stability to water is stronger, which also confirms that Ga2O3's moisture resistance is indeed very good. The electronic conductivity of electrolytes prepared with different doping ratios was tested by DC polarization. It can be found that the electronic conductivity decreased after doping, which can prove that the introduction can inhibit the transmission of electrons and the formation of lithium dendrites. Li / SSE / SS asymmetric batteries were assembled and CV tests were performed. At the same time, Li / SSE / Li symmetric batteries were assembled for CCD tests and constant current charge and discharge tests. The results all show that after Ga2O3 doping, the stability of the electrolyte and lithium negative electrode interface has been improved. At the same time, NCM811 / SSE / Li all-solid-state batteries were assembled, and the impedance before and after the cycle was tested. The full battery assembled using LPSC-0.05 had a small impedance change and the battery was relatively stable. In addition, the rate performance and long cycle performance at a rate of 0.5C were tested. At a rate of 0.5C, the initial discharge capacity of the LPSC-0.05 all-solid-state lithium metal half-cell was 135.68 mAh g –1 The capacity retention rate is as high as 91.2%, which is much higher than the initial discharge capacity of 89.06 mAh g of the LPSC full cell. –1 and a capacity retention rate of 67.3%. This fully demonstrates the potential of Ga2O3 for modified solid electrolytes and all-solid-state batteries.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A gallium oxide doped argyrodite solid electrolyte, characterized in that: Its chemical formula is Li 6.1 P 0.95 Ga 0.05 S 4.925 O 0.075 Cl.

2. The method for preparing the gallium oxide doped argyrodite solid electrolyte according to claim 1, characterized in that: Li2S, P2S5, LiCl and Ga2O3 are mixed and ball-milled, cold-pressed into sheets, sintered at high temperature, naturally cooled to room temperature, ground and sieved to obtain the sheet.

3. The preparation method according to claim 2, characterized in that: The molar ratio of Li2S, P2S5, LiCl and Ga2O3 is 5.1:0.95:2:0.

05.

4. The preparation method according to claim 2, characterized in that: The ball milling conditions are as follows: first set the machine to rotate forward at 200 r / min for 1 hour, pause for 30 minutes, reverse for 1 hour, pause for 30 minutes, and repeat the cycle for a total of 10 hours of low-speed ball milling to evenly mix the raw materials; then set the machine to rotate forward at 400 r / min for 1 hour, pause for 30 minutes, reverse for 1 hour, pause for 30 minutes, and repeat the cycle for a total of 40 hours of high-speed ball milling.

5. The preparation method according to claim 2, characterized in that: The specific method of high-temperature sintering is: sintering treatment is carried out in a tubular furnace, the time from 30°C to 500°C is set to 235min, the heating rate is set to 2°C / min, 500°C is kept for 300min, and then naturally cooled to room temperature.

6. Use of the solid electrolyte according to claim 1 in the preparation of composite positive electrode materials.

7. A composite positive electrode material, characterized in that: Comprising the solid electrolyte according to claim 1.

8. Use of the solid electrolyte according to claim 1 or the composite positive electrode material according to claim 7 in the preparation of a solid-state battery.

9. A solid-state battery, characterized in that: A positive electrode made of the composite positive electrode material according to claim 7.